Development of P5 Module Based nn Experiential Learning “Recycling Plastic Waste” on the Theme of Sustainable Lifestyle of Elementary School Students - Ningsih, Umi; Arafat, Yasir; Faipri Selegi, Susanti (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
This research and development aims to develop a P5 Module Based on Experential Learning